1994
DOI: 10.1093/oxfordjournals.eurheartj.a060379
|View full text |Cite
|
Sign up to set email alerts
|

Declining hospital mortality in acute myocardial infarction

Abstract: Beta-blockers, nitrates, aspirin and thrombolytic drugs have each separately been shown to reduce mortality in acute myocardial infarction, but the effect of these treatments combined during routine coronary care has not been assessed. The coronary care unit at Ostra Hospital services a stable community of 250,000 inhabitants. Since 1984 all patients have been entered into a computerized database. In addition, information on age, sex, discharge diagnosis and hospital outcome is also available for patients admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(23 citation statements)
references
References 0 publications
1
22
0
Order By: Relevance
“…*Reference period was 1978 to 1981. This is an observational study, and no cause-effect relationship should be drawn from our findings that, however, convincingly support the effectiveness of thrombolytic and antiplatelet drugs in daily clinical practice because (1) they are biologically plausible, (2) an increasing protective effect emerges in the last 2 periods studied (when the drugs were used), (3) they are consistent with those of other studies, 6,9,14 (4) the combination of both treatments has been found to provide an optimum additive benefit, and (5) the strength of the relationship between drug use and case fatality reduction is great in terms of OR magnitude. The effect of improvements in primary care and prehospital emergency care, changes in primary prevention, and better lifestyles cannot be readily ascertained.…”
Section: Study Characteristics and Limitationssupporting
confidence: 85%
“…*Reference period was 1978 to 1981. This is an observational study, and no cause-effect relationship should be drawn from our findings that, however, convincingly support the effectiveness of thrombolytic and antiplatelet drugs in daily clinical practice because (1) they are biologically plausible, (2) an increasing protective effect emerges in the last 2 periods studied (when the drugs were used), (3) they are consistent with those of other studies, 6,9,14 (4) the combination of both treatments has been found to provide an optimum additive benefit, and (5) the strength of the relationship between drug use and case fatality reduction is great in terms of OR magnitude. The effect of improvements in primary care and prehospital emergency care, changes in primary prevention, and better lifestyles cannot be readily ascertained.…”
Section: Study Characteristics and Limitationssupporting
confidence: 85%
“…Previous analyses suggested that some of the decline in case fatality was due to increased use of thrombolytic therapy. 4,20 Other therapies with established impact on AMI survival, such as aspirin, 21 ACE inhibitors, 22 ␤-blockers, 23,24 anticoagulants, 25 and emergency angioplasty were also used much more frequently in 1995 than in 1985. Two striking features of the trends in the short-term care of hospitalized AMI presented here are (1) their consistency with published results of major clinical trials in the same period and (2) the little to no sex difference in medical intervention in AMI patients in 1995.…”
Section: Discussionmentioning
confidence: 99%
“…Our knowledge about patients who are hospitalised and discharged with a diagnosis of acute myocardial infarction, including data relating to risk factors for mortality [1][2][3], the efficacy of various treatments [4][5][6] and prognosis [7,8], is extensive.…”
Section: Introductionmentioning
confidence: 99%